(untitled) (Nigerian Journal of Physiological Sciences, 2024)
Many biological tissues and organs are affected by the toxicity of potassium bromate (KBrO3). The purpose of this study was to evaluate the Parkia Biglobosa (P. Biglobosa) seed’s ability to treat KBrO3-induced haematological parameters derangement. After becoming accustomed to the lab, 24 Wistar rats were randomly assigned to groups A, B, C, and D. Group A was given distilled water to drink. Each of the groups in B, C, and D got 100 mg/kg of KBrO3. Also, for 28 days prior to sacrifice, groups C and D received 100 and 200 mg/kg of P. biglobosa, respectively. Blood was drawn, and the haemogram was examined using a haematology autoanalyzer. When KBrO3 was added compared to the control, the results showed a substantial decrease in both haemoglobin concentration, packed cell volume (PCV), and red blood cell count from 17.262.84 g/dL, 39.732.58%, 5.120.83 x 1012/L to 13.251.25 g/dL, 27.931.44%, and 3.470.22 x 1012/L, respectively. The effect of KBrO3 was dose-dependently counteracted by P. biglobosa treatments of 100 and 200 mg/kg body weight. However, there was no discernible difference in the MCV, MCH, and MCHC values between the control and test groups. Similar to how P. biglobosa reduced the effects of KBrO3 in a dose-dependent manner, P. biglobosa also induced a substantial decrease in white blood cell count, its differentials, and platelet counts (P0.05). KBrO3-induced deranged haematological parameters were mitigated by Parkia biglobosa in a dose-dependent manner. Care must be taken with the consumption of this addictive due to its numerous toxic effects. However, consumption of P. biglobosa, a tropical homemade food is recommended for families to benefit from the barrage of its health benefits. This will also alleviate the toxic effect of KBrO3 if consumed inadvertently. Human clinical trial is needed to substantiate these findings